PENGARUH IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 55 TAHUN 2022, PENGETAHUAN PERPAJAKAN, DAN KESADARAN WAJIB PAJAK PADA KEPATUHAN WAJIB PAJAK (Studi pada UMKM di Kabupaten Gianyar) - Dea Ayu Heggar Rinjani Charal; Ni Luh Supadmi (Jurnal Ekonomi dan Bisnis, 2025)
This research seeks to empirically examine the impact of Government Regulation Number 55 of 2022, tax literacy levels, and taxpayer awareness on the tax compliance of MSME actors in Gianyar Regency. A descriptive quantitative method with a causal approach was employed. The study was conducted at the Gianyar Pratama Tax Office, involving a population of 4,752 MSME taxpayers registered at the office. The sample was selected using an accidental sampling technique, resulting in 98 respondents, determined through the Slovin formula. The collected data were processed using multiple linear regression analysis. The findings indicate that the implementation of the regulation, tax knowledge, and taxpayer awareness all have a significant and positive influence on MSME tax compliance. This implies that higher trust in the regulation's benefits, better understanding of taxation, and greater awareness of its importance lead to increased compliance in fulfilling tax obligations.